PENGARUH FAKTOR NON TEKNIS PERTANDINGAN DALAM PENILAIAN JURI KEPADA ATLET PENCAK SILAT - Wahyudi, Achmad Rizanul; Natalia, Adinda Ayu (Universitas Negeri Surabaya, 2021)
The judging process which is considered closed is able to give distorted thoughts from the coaches and athletes of pencak silat. Some argue that there are other factors that can influence the judges' judgment when judging athletes. Based on the explanation above, the researchers made a study entitled